Introduction to the Musical Composition “Bangked” | Pengantar Komposisi Karawitan “Bangked” - I Made Dandy Pradana; Suharta I Wayan (Pusat Penerbitan LPPMPP ISI Denpasar, 2023)
Bangked's karawitan artwork is work inspired by the formation of paddy mud and the cili motive found in lamak which is still closely related to the formation of the mud itself. Bangked is a Balinese word that means the combination of two elements, namely, land and water. Rare cili and rare angon are depictions of these two elements which farmers usually depict in the form of scarecrows or scarecrows. The purpose of creating Bangked's artwork is to give a message of advice to all of society so that we as humans must be able to appreciate land and water as elements in life. Bangked's artwork uses the barungan semara pegulingan saih pitu as a medium of expression due to the many modulations or patet that the stylist can use to express all the inspiration that is in the stylist's mind. The method for creating Bangked karawitan works of art uses the Panca Stihiti Ngawi Sani method from I Wayan Dibia, which includes the Inspiration Stage (Ngawirasa), Exploration Stage (Ngawacak), Conception Stage (Ngerencana), Execution Stage (Ngewangun), and the third. last Production Stage (Ngebah/Maedeng). In this Bangked karawitan artwork, a division system is used, in which each part has its own meaning and significance.